Ancaman Penyalahgunaan Data Pribadi sebagai Dampak Penggunaan Sistem Informasi Manajemen - Raihan Aulia Nugraha; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
This research aims to analyze the threat of misuse of personal data as a result of the use of management information systems. This research uses qualitative research methods and library research. All scientific article data comes from Google Scholar and other online media and ranges from the last 5 years, namely 2020 to 2024. The research results show that data theft is usually carried out with the aim of seeking financial benefits, reputation, and so on. In dealing with misuse of technology, Indonesia does not yet have specific laws that regulate the protection of personal data in an integrated manner, however there are several laws and regulations that regulate personal data, such as Minister of Communication and Information Regulation No. 20 of 2016 concerning Protection of Personal Data in Electronic Systems and Law no. 24 of 2013 concerning Population Administration. Legal protection of consumer personal data takes the form of administrative sanctions for service providers who violate the provisions based on Article 36 Paragraph (1) of Minister of Communication and Information Regulation No. 20 of 2016 and criminal sanctions in accordance with the provisions of Article 95A of Law No. 24 of 2013.